Community-based elderly care approaches implemented in low and middle-income countries: A scoping review. - Haufiku-Weyulu, Mouyelele.; Mahalie,Roswitha.; Aku-Akai, Larai. (Research Journal of Health Sciences, 2025)
Introduction: Globally, the average lifespan has become prolonged in recent years. Strong community-based care services (CBCS) are imperative to maintain the health of older persons when family care falls short. Data on the health and care of older persons in low—and middle-income countries (LMICs) like Namibia are scarce. The review aimed to map the available evidence on CBC approaches implemented in LMICs. Methodology: The review followed the 2022 Joanna Briggs Institute (JBI) manual for Evidence Synthesis. Rayyan cloud-based software was used to organize, manage, and remove duplicates. The Preferred Reporting Items for Systematic Review and Meta-Analysis Extension for Scoping Reviews (PRISMA-ScR) were utilized to convey the review's results. Results: The final analysis included 22 articles. Households with older people need extra income to maintain a similar living standard to those without. LMICs face challenges in building comprehensive and sustainable frameworks to support the older population, struggle to provide adequate pensions, have a significant shortage of skilled geriatrics, and rely on informal caregivers as care homes and primary health care systems are insufficient. Conclusion: As the challenge of population aging intensifies, strengthening CBC approaches is essential, given that most older persons prefer to age at home rather than in facilities
Keywords: Elderly; Older persons; Community based; Elder care; Low- and middle-income countries